Transposon insertions causing constitutive sex-lethal activity in Drosophila melanogaster after Sxl sex-specific transcript splicing. - Bernstein, M.; Lersch, R.A.; Subrahmanyan, L.; Cline, T.W. (Genetics, 1995)
Sex-lethal (Sxl) gene products induce female development in Drosophila melanogaster and suppress the transcriptional hyperactivation of X-linked genes responsible for male X-chromosome dosage compensation. Control of Sxl functioning by the dose of X-chromosomes normally ensures that the female-specific functions of this developmental switch gene are only expressed in diplo-X individuals. Although the immediate effect of X-chromosome dose is on Sxl transcription, during most of the life cycle "on" vs. "off" reflects alternative Sxl RNA splicing, with the female (productive) splicing mode maintained by a positive feedback activity of SXL protein on Sxl pre-mRNA splicing. "Male-lethal" (SxlM) gain-of-function alleles subvert Sxl control by X-chromosome dose, allowing female Sxl functions to be expressed independent of the positive regulators upstream of Sxl. As a consequence, SxlM haplo-X animals (chromosomal males) die because of improper dosage compensation, and SxlM chromosomal females survive the otherwise lethal effects of mutations in upstream positive regulators. Five independent spontaneous SxlM alleles were shown previously to be transposon insertions into what was subsequently found to be the region of regulated sex-specific Sxl RNA splicing. We show that these five alleles represent three different mutant types: SxlM1, SxlM3, and SxlM4. SxlM1 is an insertion of a roo element 674 bp downstream of the translation-terminating male-specific exon. SxlM3 is an insertion of a hobo transposon (not 297 as previously reported) into the 3' splice site of the male exon, and SxlM4 is an insertion of a novel transposon into the male-specific exon itself. We show that these three gain-of-function mutants differ considerably in their ability to bypass the sex determination signal, with SxlM4 being the strongest and SxlM1 the weakest. This difference is also reflected in effects of these mutations on sex-specific RNA splicing and on the rate of appearance of SXL protein in male embryos. Transcript analysis of double-mutant male-viable SxlM derivatives in which the SxlM insertion is cis to loss-of-function mutations, combined with other results reported here, indicates that the constitutive character of these SxlM alleles is a consequence of an alteration of the structure of the pre-mRNA that allows some level of female splicing to occur even in the absence of functional SXL protein. Surprisingly, however, most of the constitutive character of SxlM alleles appears to depend on the mutant alleles' responsiveness, perhaps greater than wild-type, to the autoregulatory splicing activity of the wild-type SXL proteins they produce.